Building end to end service guarantee system of IoT covering“terminal pipe and cloud” based on signaling big data - Xuli YE; Qiang ZENG; Liyu LIU; Yu SU; Meng KANG (物联网学报)
With the evolution of wireless communication service types to massive,large connections,small traffic scenarios,mobile Internet has marched into the Internet of things.Carrying on business networking wireless network deployment in communication operators,which provides a wealth of industry applications also enable operators facing huge end-to-end backward challenges to business.An end to end service guarantee system based on the signaling big data and covering the “terminal pipe and cloud” was proposed and constructed,and the six network dimensions in the user,terminal,wireless,transmission,core network and digital network was solved,as well as the four stages of network access,service access,network switching,and service quality of six dimensions and four stages facing the Internet of things.In order to solve the problem of inter professional collaboration and demarcation,the assistant operator completes the transformation from the traditional KPI (key performance indicator) index mode to the service aware KQI (key quality indicator) end to end full process business guarantee mechanism,and provides the end to end full process one key positioning ability guarantee for the Internet of things applications.